“Pre germinación inducida con enraizador (acido giberélico), y el comportamiento en campo de bulbos, rizomas principales y rizomas secundarios de curcuma longa en el distrito d eSan José de sisa, region San Martín” - Ishuiza Rodas, Geiler (2011)
The objectives of the present investigation work were to evaluate the pre germination of three parts (bulbs, main and secondary rhizomes) of vegetative seed of Curcuma longa, induced to pre germination using an inductor (Sour Giberélico), the agronomic variables (days to the pre germination, emergency, plant height, days to the floración, it harvests, weight of fresh rhizomes, number of rhizomes for blow, longitude and diameter of rhizomes, yield), during the development of the cultivation of Curcuma longa the induction of an inductor and to determine the production costs and the profitability of the cultivation of Curcuma longa for each treatment. from October of the 2006 until Julio the 2007. The investigation work was carried out in the parcel of the producing Sixto Castillo Saucedo to 1.5 Km. of the district of San José of Excise county the Gilding. Producing beneficiary of the project "Sustainable Production of the toothpick (Curcuma longa), in the valley of the river it Pilfers, Region San Martín" the same one that CAPIRONA. Executes. lt was applied the design of Blocks Completely Randomizado (DBCR), in field, both with factorial arrangement 2 x 3 with a total of 18 experimental units including the witness. Of this experiment you concludes: that the method of pre germination of the seeds with inductores is ideal to accelerate the germination and emergency of the three types of seeds of Curcuma longa, in a same way this rebounds in the days to the floración, making that the cultivation is developed quickly to cutting its cycle. On the other hand as for characteristic agronomic they highlighted the bulbs with inductor. To other as for the yield of fresh rhizome the seeds of bulbs with inductor and the main rhizomes with inductor and without inductor they obtained the highest averages in 25916,67; 23583,33 and 23400 kg/Ha respectively. But when carrying out the drying the biggest yield they obtained it the main rhizomes without inductor and with inductor, followed by the bulbs with and without inductor with 5923,33; 5666,67; 5250 and 4616,67 Kg/Ha respectively. Of these one can say that the inductores helps accumulate bigger humidity in the bulb seeds more than in the main rhizomes. With regard to the curcumina percentage, the seeds tried with inductor obtained percentages statistically same that the seeds that were not treated with inductor. with the seed of main rhizome without inductor the biggest benefit cost is obtained investing a sun since you this livestock s/3, 18 n/s, with the main siembra of rhizomes with enraizador, bulb con inductor and bulbs without inductor a benficio s/2,84 cost is obtained; s/2,56 and s/2,26 nis respectively. with the seeds of secondary rhizomes when investing a sun you this livestock s/0,77 and s/0,82 n/s respectively.